1982
DOI: 10.1007/bf00304544
|View full text |Cite
|
Sign up to set email alerts
|

Sister chromatid exchanges and structural chromosome aberrations in relation to age and sex

Abstract: Sister chromatid exchanges (SCE) and structural chromosome aberrations were analyzed in peripheral blood lymphocytes of 100 individuals, and correlated to age and sex. No correlation was found between the frequency of SCE and age, but older individuals had significantly more structural aberrations than younger. Females had significantly more SCE as well as structural chromosome aberrations than males. The positive correlations of SCE and structural aberrations to age and sex were also significant when these fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

1984
1984
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(18 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…Literature and personal data suggest an increase in spontaneous chromosome abnormalities frequency in healthy controls with age. 27,28 Therefore, for the statistical analysis we consider two groups of control subjects. In the first group (age 5 -49), the frequency of cells with aberrations varies between 0 and 9.1% with a mean value of 5.4% and a standard deviation (SD) of 2.9, while in the second group (age 60 -90), the frequency of cells with abnormalities ranges between 4 and 14% with a mean value of 9.2% and an SD of 3.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature and personal data suggest an increase in spontaneous chromosome abnormalities frequency in healthy controls with age. 27,28 Therefore, for the statistical analysis we consider two groups of control subjects. In the first group (age 5 -49), the frequency of cells with aberrations varies between 0 and 9.1% with a mean value of 5.4% and a standard deviation (SD) of 2.9, while in the second group (age 60 -90), the frequency of cells with abnormalities ranges between 4 and 14% with a mean value of 9.2% and an SD of 3.5.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that in normal subjects, the level of induced apoptosis depends on the age of the donors 30 and that the frequency of chromosome alterations in peripheral blood lymphocytes increases with age. 27,28 A decrement with the age in the ability of programmed death for cells with chromosome abnormalities could explain both the high frequency of chromosome rearrangements present in healthy donors over 60 and the higher risk to develop a cancer with increasing age. Chromosome instability in NBS patients' parents and relatives has been rarely investigated: some authors report no chromosome abnormalities, 31 -33 while others describe the presence of chromosome rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…Esses achados estão de acordo com os observados por vários autores (Bender et al, 1988;Galloway et al, 1986;Hedner et al, 1982;Margolin & Shelby, 1985), enquanto que outros autores não encontraram nenhum efeito com relação ao sexo (Anderson et al, 1991).…”
Section: Discussionunclassified
“…Previous studies [10,14] have reported age as a significant factor affecting chromosome aberrations. Our results indicate that not only age but also sex may be involved; i.e.…”
Section: Discussionmentioning
confidence: 99%